Analisis Kualitas Briket Berbahan Dasar Cangkang Kemiri - fallo, Gideon; Riwu, Defmit B.N.; Koehuan, Verdy A. (Universitas Nusa Cendana, 2024)
The increasing use of fossil fuels, which is aware of the issue of global warming and environmental damage due to pollution, has increased efforts to develop renewable energy sources. Briquettes are one of the alternative sources of renewable energy that have been developed this decade. This research is part of an effort to develop briquettes, especially hazelnut shell briquettes, as an alternative fuel. Making hazelnut shell charcoal briquettes is carried out by carbonization process using the pyrolysis method. Making starch adhesive (tapioca starch) with a ratio of charcoal powder and starch adhesive (tapioca flour) of 90:10%. Furthermore, the candlenut shell briquettes were tested for proximation tests (ash content, moisture content and calorific value). Candlenut shell briquettes can be used as an alternative fuel because they have a high calorific value of 6061kcal/kg. The hazelnut shell briquettes basically comply with the Indonesian National Standard SNI 01-6235-2000 and the Emission Standards of the Regulation of the State Minister for the Environment Number 05 of 2006 regarding the threshold for exhaust emissions of old motorized vehicles.